THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY, EXPIRED DATE, AND PERCEPTION DECISION ON THE PURCHASE DECISION OF SARI ROTI PRODUCTS - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
The purpose of this study was to analyze the effect of brand image, product quality, expired date, and perception decision on purchasing decisions for sari roti products. The population in this study are student collage institute of business and technology in the city of Pekanbaru. The sampling technique used was the Solvin method, sample size of this study was 96 respondents. The data collection techniques used a questionnaire and literature study, Data analysis technique used (normality test, heteroscedasticity test, multicollinearity test), statistical test (t test, F test, determination coefficient test). The results of this study indicate that brand image, product quality, expired date, and perception decision a positive and significant effects on purchasing decisions for Sari Roti in the student collage institute of business and technology pekanbaru. Brand image are the most dominant variable in influencing consumer purchasing decisions.